Intermediate-regulated dynamic restructuring at Ag-Cu biphasic interface enables selective CO2 electroreduction to C2+ fuels - Gao, Xinyang (2025)
A bimetallic heterostructure has been shown effective to enhance the multi-carbon (C2+) product selectivity in CO2 electroreduction. Clarifying the interfacial structure under electrolysis and its decisive role in the pathway selection are crucial, yet challenging. Here, we conceive a well-defined Ag-Cu biphasic heterostructure to understand the interfacial structure-steered product selectivity: The Cu-rich interface prefers ethylene, while the dominant product switch to alcohols with an increasing Ag fraction, and finally to CO as Ag occupying the main surface. We unravel a *CO intermediate-regulated interfacial restructuring, and observe abundant of Cu atoms migrating onto the neighboring Ag surface under a locally high *CO concentration. The evolving structure alters the oxyphilic characteristic at the interface, which profoundly determines the hydrogenation energetics of CO2 and ultimately, the dominant C2+ product. This work explicitly links the evolving interfacial structure with distinct C2+ pathway, formulating design guidelines for bimetallic electrocatalysts with selectively enhanced C2+ yields.